O cônjuge acompanhante é o homem: compreendendo a experiência masculina na expatriação de sua esposa executiva - Rapôso, Lecticia Maria Zambrano de Araújo (2014)
The growth of feminine access to high end positions in the corporate world is a global phenomenon which enables women to reach promotions and expatriation opportunities as well as the traditional group of men in corporate jobs.This dissertation´s goal is to know and understand the experience of men´s lives as an accompanying life partner during the expatriation of their wives, attempting to comprehend the differences in experiences.It is a qualitative study which used the life-story method to investigate the lives of three childless men in their thirties who interrupted their careers in order to follow their wives in a new country. Results confirm and broaden previous research papers helping us better understand the connections of themes such as expatriation, double career marriages and gender studies. Personal traits and shared decisions were aspects seen to favor adaptation in foreign countries. Double-career marriages seem to be unique and express a specific manner of functioning through flexible deals and more creative solutions when searching for solutions to achieve mutual satisfaction. The challenges of masculinity, considering the men are temporarily out of work, seemed to be work related and brought forth by the need to internally negotiate and to negotiate with the outside world the prerogatives of belonging to a hegemonic group. This conflict is shown in the desire to keep an active career and to keep investing time and energy in a career. Results show clearly that there is felt pressure into keeping the cultural and personal concepts of masculinity, maintenance of power and the existence of social mechanisms of correction of deviated behavior